Impact of a new levonorgestrel intrauterine system, Levosert®, on heavy menstrual bleeding: results of a one-year randomised controlled trial. (June 2014) - Mawet, Marie; Nollevaux, Fabrice; Nizet, Dominique; Wijzen, Fabienne; Gordenne, Valérie; Tasev, Niso; Segedi, Dimitrije; Marinescu, Bogdan; Enache, Andreea; Parhomenko, Vadim; Frankenne, Francis; Foidart, Jean-Michel
Abstract: Objective To evaluate a new levonorgestrel-releasing intrauterine system (LNG-IUS) called Levosert ® for the treatment of heavy menstrual bleeding (HMB) in comparison to the reference product Mirena ® . Methods A multicentre, randomised, controlled trial, in non-menopausal women diagnosed with functional HMB (defined as menstrual blood loss [MBL] ≥ 80 mL) randomised to either Levosert ® or Mirena ® and followed for up to one year. MBL was evaluated using a validated modified version of the Wyatt pictogram. Results A total of 280 women were randomised (141 to Levosert ® and 139 to Mirena ® ). During the one-year treatment period, both Levosert ® and Mirena ® dramatically decreased MBL and increased haemoglobin and ferritin levels. There were no statistically significant differences between Levosert ® and Mirena ® regarding any of the parameters evaluated during the study. Similar bleeding patterns were observed in both groups. Levosert ® was inserted with the same ease as Mirena ® . Both treatments were associated with identical expulsion rates and no perforations occurred in either treatment group. Conclusion Levosert ®, a new LNG-IUS designed to release the same daily amount of LNG as Mirena ®, is highly effective in the treatment of HMB. No differences were observed between Levosert ® and Mirena ® regarding all evaluated outcomes, including safety profile.